Detection of Enteric Protozoa Parasites, E. coli Bacteriophages and Fecal Pollution Indicator Organisms in Shrimp Sold in the State of Zulia - Mariángela Bracho; Ligia Botero; Odelis Díaz Suárez; Zulbey Rivero; Azael Freites; María García; Marycarmen Soler (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2013)
The presence of G. intestinalis and C. parvum, E. coli F+ bacteriophages and fecal pollution indicator organisms was determined in shrimp for human consumption marketed in the State of Zulia. Parasites were concentrated from the digestive systems of shrimp pools, detected by formalin-ether and quantified by direct immunofluorescence. E. coli F + bacteriophage and pollution indicator organism concentrations were determined by standard techniques. In this work, G. intestinalis, C. parvum, E. coli F + bacteriophages and E. coli were detected in shrimp for human consumption marketed in the State of Zulia that met the quality criteria of Venezuelan health and safety regulations. 91.5% of the samples analyzed were positive for G. intestinalis (average: 36.6 cyst/100g), 95.3% for C parvum (average: 32.8 oocyst/100g), 100% for E coli F + bacteriophages (average: 2.8 x 103 FPFU/100g) and 71.5% for E. coli (average: 4.3 x 104 MPN/g). Results of this research indicate that shrimp can become a vehicle for transmitting pathogens to humans and demonstrate the need for including a parasitic and viral parameter in microbiological quality control for seafood.